Balandra Bay, Trinidad, B.W.I. - 408 - (:unkn) unknown (My University, 2009)
Balandra Bay lined with tall coconut trees and the mild surf washing the sandy shore. The postcard is addressed to Francis (last name illegible), California, U.S.A. Postmarked June 4, 1947.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Balandra Bay; Beaches--Trinidad and Tobago; Coasts--Trinidad and Tobago; 1947; Bays--Trinidad and Tobago